2008
DOI: 10.1016/j.ejheart.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Gender related differences in patients presenting with acute heart failure. Results from EuroHeart Failure Survey II

Abstract: Aims: This analysis evaluates the gender differences in patients hospitalised for acute heart failure (AHF) in the EuroHeart Failure Survey II (EHFS). Results: Of the 3580 patients included in EHFS II, 1384 (39%) were women, mean age 73 years. 2196 (61%) were men, mean age 68 years. Women more frequently had new-onset AHF, hypertension and valvular disease and less frequently coronary heart disease or dilated cardiomyopathy compared with men. Smoking, chronic obstructive pulmonary disease, peripheral arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
132
4
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 30 publications
29
132
4
5
Order By: Relevance
“…In that study 73.2% of patients had HFrEF, which reflects considerable differences between the two study populations and is evidence of how observational studies provide valuable information about acute HF managed in different clinical scenarios. 20,21 Our data on gender are in agreement with other reports showing that elderly patients hospitalized with HF are mainly women 22 and that patients with HFpEF are older and more often female than those with HFrEF. 1,5,6,8,13 HF patients managed by internists are more likely to have the characteristics of those managed by general practitioners.…”
Section: Discussionsupporting
confidence: 92%
“…In that study 73.2% of patients had HFrEF, which reflects considerable differences between the two study populations and is evidence of how observational studies provide valuable information about acute HF managed in different clinical scenarios. 20,21 Our data on gender are in agreement with other reports showing that elderly patients hospitalized with HF are mainly women 22 and that patients with HFpEF are older and more often female than those with HFrEF. 1,5,6,8,13 HF patients managed by internists are more likely to have the characteristics of those managed by general practitioners.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, gene disruption of FKBP12.6, phospholamban, and ERa revealed a cardiac phenotype with male preponderance [42][43][44]. Studies with patients hospitalized for acute heart failure in the EuroHeart Failure Survey II revealed that men had DCM more frequently than women [45]. The exact molecular mechanism is still unknown, but the hypothesis is that estrogen prevents the development of cardiovascular diseases that could culminate into CHF [37].…”
Section: Discussionmentioning
confidence: 99%
“…A valvular origin of heart failure, such as aortic stenosis, was more common in women than in men. 28,29 However, some studies of Caucasian patients found that male gender was a prognostic factor for the development of aortic stenosis, 6,7 whereas others found no influence of gender. 11,20 The effects of gender on coronary artery calcification differed even between patient cohorts from the Western countries.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdmentioning
confidence: 99%